Improving The Order Pickup Process in Warehouses by Instant Couriers Through Zone-Based Assignment - Danti Ardianti Soesanto; Valeriana Lukitosari (MASI Mandiri Edukasi, 2026)
The expansion of e-commerce has intensified operational pressures on warehouse logistics, particularly for instant-delivery services, where speed and accuracy are critical. At Warehouse A of Marketplace ABC, the order pickup process experienced inefficiencies due to alphabetical sorting and courier assignments that were not aligned with the physical order placement, resulting in longer pickup times and frequent errors. This study aims to optimize the instant courier pickup process by redesigning order sorting and courier assignment through zone picking based on delivery location similarity. An applied quantitative case study was conducted using 61,577 historical instant delivery orders from July 2025. Delivery locations were clustered using K-means, and the optimal number of zones was determined using the Elbow method. The analysis yielded five optimal picking zones, which were subsequently implemented in the warehouse pickup workflow. The redesigned process significantly improved operational performance, reducing the average pickup time from 6.7 minutes to 1.7 minutes and achieving 100% pickup accuracy. These findings confirm that integrating zone picking with clustering-based zoning effectively enhances efficiency and accuracy in instant courier warehouse operations.